Positive electrode material, positive electrode plate and secondary battery
By introducing a specific distribution of element M and an appropriate amount of free nitrate ions into the positive electrode material of the lithium-ion battery, the problem of capacity loss and insufficient cycling performance of the lithium-ion battery at high voltage is solved, and higher structural stability and battery performance are achieved.
Patent Information
- Application Number
- CN202411981769.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
AI Technical Summary
The capacity loss and cycling performance of existing lithium-ion batteries at high voltages are insufficient, and it is urgent to improve the cathode material to improve the performance of the battery.
A positive electrode material is provided, containing element M (selected from Group IA and Group IIA metal elements), whose distribution in the particles satisfies 1.2≤X2/X1≤20, and contains 10 ppm≤N1≤100 ppm free nitrate ions.
By controlling the distribution of element M and the content of free nitrate ions, the structural stability and cycling performance of the positive electrode material at high voltage are improved, and the capacity and rate performance of the battery are enhanced.
Smart Images

Figure CN119650687A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material, a positive electrode sheet and a secondary battery. Background Art
[0002] With the increasing popularity and development of electric vehicles, the market demand for lithium-ion batteries continues to increase, especially in terms of driving range, service life and driving safety.
[0003] At present, people have increasingly higher requirements on the energy density, safety, and cycle performance of lithium-ion batteries. There is an urgent need to improve the positive electrode materials in lithium-ion batteries in order to improve the capacity loss and cycle performance of existing lithium-ion batteries under high voltage. Summary of the invention
[0004] In view of this, in order to solve at least one of the above defects, it is necessary to provide a positive electrode material.
[0005] In addition, it is also necessary to provide a positive electrode sheet and a secondary battery using the above-mentioned positive electrode material.
[0006] In the first aspect, an embodiment of the present application provides a positive electrode material, wherein the positive electrode material contains an M element, wherein the element M is selected from at least one metal element in Group IA and Group IIA of the periodic table, and the distribution of the M element in the particle satisfies: 1.2≤X2 / X1≤20, wherein X1 is the concentration of the M element in the central area of the particle, and X2 is the concentration of the M element in the surface area of the particle; and the positive electrode material contains free nitrate ions, and the content of the free nitrate ions is N1, wherein 10ppm≤N1≤100ppm.
[0007] In some possible embodiments, based on the mass of the positive electrode material, the mass content of the M element is 10 ppm to 400 ppm.
[0008] In some possible embodiments, X1 is 10ppm~50ppm; and / or X2 is 300ppm~400ppm.
[0009] In some possible embodiments, the distribution of the M element in the particles satisfies: 6≤X2 / X1≤11; and. Or, the content N1 of the free nitrate ions is 60ppm~100ppm.
[0010] In some possible embodiments, during the first cycle of charge and discharge, the structural recovery degree δ of the secondary battery prepared from the positive electrode material satisfies: 100.00% ≥ δ ≥ 99.70%, wherein δ = θ1 / θ2 × 100%, θ1 is the diffraction characteristic peak position of the (003) peak at the beginning of the first cycle of charging, and θ2 is the diffraction characteristic peak position of the (003) peak at the end of the first cycle of discharging.
[0011] In some possible embodiments, the general formula of the positive electrode material is as follows: Li a Ni b Co c Q d M (1-b-c-d-e) N e O2, wherein 0.95≤a≤1.2, 0.5<b≤1, 0≤c≤0.25, 0<d≤0.45, b+c+d<1, 0<e<0.1, Q includes at least one of Mn and Al, and the N element is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, Y, La, Nb and Mo.
[0012] In some possible embodiments, the particle size distribution width of the positive electrode material satisfies: 1.0≤(D90-D10) / D50≤1.5.
[0013] In some possible embodiments, the lattice strain ε of the positive electrode material is less than 0.1%.
[0014] In some possible embodiments, the specific surface area of the positive electrode material is 0.4 m 2 / g~0.9m 2 / g.
[0015] In some possible embodiments, the tap density ρ1 of the positive electrode material is 2.0 g / cm 3 ~3.0g / cm 3 .
[0016] In some possible embodiments, the powder compaction density ρ2 of the positive electrode material is 2.8 g / cm 3 ~4.0g / cm 3 .
[0017] In some possible embodiments, the free lithium content of the positive electrode material is 400 ppm to 600 ppm.
[0018] In some possible embodiments, the positive electrode material is a single crystal positive electrode material, and the average particle size of primary particles of the positive electrode material is 1 μm to 5 μm.
[0019] In a second aspect, an embodiment of the present application provides a positive electrode plate, comprising the positive electrode material as described above.
[0020] In a third aspect, an embodiment of the present application provides a secondary battery, including an electrode assembly, wherein the electrode assembly includes a positive electrode plate, a separator and a negative electrode plate, the separator is arranged between the positive electrode plate and the negative electrode plate, and the positive electrode plate includes the positive electrode material as described above.
[0021] The positive electrode material provided in the embodiment of the present application controls the concentration of the element M in the particle to satisfy 1.2≤X2 / X1≤20, so that the content of the element M near the surface area of the particle is relatively high, and the element M increases the unit cell volume of the surface area of the particle, while the content of the element M near the center area of the particle is relatively small, so that the unit cell volume at the center area of the particle is relatively small, thereby forming a compressive stress from the surface to the center of the particle. In the process of high-voltage cycle performance, the compressive stress of the particle can alleviate the structural collapse caused by the expansion and contraction of the lattice during the deintercalation of lithium ions, and the particles are less likely to produce microcracks during long-term cycles, and can also inhibit the expansion of cracks, thereby improving the high-voltage cycle performance of the material. In addition, during charging and discharging, since the unit cell volume is in a contracted state, the compressive stress caused by the deintercalation of lithium ions during charging and discharging can be balanced, making the material structure more stable, so that the positive electrode material can have a higher ability to deintercalate lithium and a structural recovery ability during charging and discharging, so that the positive electrode material can exert a higher capacity during charging and discharging.
[0022] At the same time, the positive electrode material contains free nitrate ions, and the content of free nitrate ions is controlled to meet 10ppm≤N1≤100ppm. While improving the structural stability of the positive electrode material, the nitrate ions can induce Li ions to form a Li2O stable interface protection layer on the surface of the positive electrode material, reduce the side reactions between the electrolyte and the surface of the positive electrode material, thereby comprehensively improving the capacity, rate and cycle stability of the battery prepared using the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.
[0024] Figure 2 It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.
[0025] Figure 3 This is a definition diagram of the central area and surface area of a single crystal particle when testing the concentration distribution of the M element in the positive electrode material in this application.
[0026] Figure 4 This is a SEM image of the positive electrode material prepared in Example 1 of the present application.
[0027] Figure 5This is a SEM image of the positive electrode material prepared in Comparative Example 1 of the present application.
[0028] Figure 6 This is a distribution diagram of the Mg element inside the particles of the positive electrode material prepared in Example 1 of the present application.
[0029] Figure 7 This is a distribution diagram of the Mg element inside the particles of the positive electrode material prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0030] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0031] The present application provides a positive electrode material, wherein the positive electrode material contains an M element, wherein the M element is selected from at least one metal element in Group IA and Group IIA of the periodic table, and the positive electrode material comprises a plurality of particles, wherein the distribution of the M element in the particles satisfies: 1.2≤X2 / X1≤20, wherein X1 is the concentration of the M element in the central region of the particles, and X2 is the concentration of the M element in the surface region of the particles; in addition, the positive electrode material contains free nitrate ions (NO3 - ), the mass content of free nitrate ions is N1, where 10ppm≤N1≤100ppm. The positive electrode material of the embodiment of the present application has high structural stability under high voltage and is not prone to microcracks in long-term cycle tests, thereby effectively improving the cycle performance of the positive electrode material.
[0032] The embodiment of the present application first introduces metal elements (i.e., M elements) in Group IA and Group IIA of the periodic table into the particles, and controls the distribution of M elements in the central area and the surface area of the particles to satisfy: 1.2≤X2 / X1≤20, so that the content of element M near the surface area of the particles is relatively high, and the element M increases the unit cell volume of the surface area of the particles, while the content of element M near the center area of the particles is relatively low, so that the unit cell volume in the center area of the particles is relatively small, thereby forming a compressive stress from the surface to the center of the particles. In the process of high voltage cycling performance, the compressive stress of the particles can alleviate the structural collapse caused by lattice expansion and contraction during the lithium ion insertion and extraction process, and in During long-term cycling, the particles are less likely to produce microcracks and can inhibit the expansion of cracks, thereby improving the high-voltage cycling performance of the positive electrode material; by controlling the content of free nitrate ions in the positive electrode material to meet 10ppm≤N1≤100ppm, the presence of an appropriate amount of free nitrate ions in the positive electrode material is beneficial to inhibiting the volume change of the positive electrode material during the charging and discharging process. The inventors speculate that this is because the free nitrate ions in the positive electrode material will induce the formation of a Li2O stable interface protection layer (CEI film) on the surface of the positive electrode material during the first charging and discharging process, thereby inhibiting the volume change of the positive electrode material during the charging and discharging process, thereby further improving the high-voltage cycling performance of the positive electrode material.
[0033] Exemplarily, the ratio of X2 / X1 can be 1.2, 1.5, 2, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any value within the range formed by any two of the above values. Furthermore, the distribution of the M element in the particles of the positive electrode material satisfies: 6≤X2 / X1≤11, which is conducive to further improving the capacity, cycle stability and rate performance of the prepared battery, and further reducing the gas production.
[0034] When X2 / X1<1.2, the particle surface unit cell volume and the internal unit cell volume are evenly distributed, and the average unit cell volume of the particle is relatively large, which is not easy to produce compressive stress and is not conducive to improving the long-term cycle performance of the secondary battery. When X2 / X1>20, too much element M will be enriched in the surface area of the particle, occupying the lattice lithium site, affecting the transmission and diffusion of lithium ions, and reducing the rate performance of the secondary battery.
[0035] In the embodiment of the present application, the content of free nitrate ions in the positive electrode material is controlled to satisfy 10ppm≤N1≤100ppm. The presence of an appropriate amount of free nitrate ions in the positive electrode material is beneficial to suppressing the volume change of the positive electrode material during the charge and discharge process. The inventors speculate that the free nitrate ions in the positive electrode material will induce the formation of a Li2O stable interface protection layer (CEI film) on the surface of the positive electrode material during the first charge and discharge process. The specific reaction formula is: , Li2O has high voltage resistance, which helps to improve the high voltage resistance of the positive electrode material, inhibit the volume change of the positive electrode material during the charge and discharge process, and further improve the high voltage cycle performance of the positive electrode material. If the mass content of the free nitrate of the positive electrode material is too high, too much Li2O will be formed on the surface of the positive electrode material, which will hinder the ion transmission of the positive electrode material. When the mass content of the free nitrate of the positive electrode material is too low, the amount of Li2O formed on the surface of the positive electrode material is too small, and the side reaction between the positive electrode material and the electrolyte is aggravated, especially under high voltage charge and discharge conditions, the capacity loss of the positive electrode material is aggravated. The present application controls the mass content of the free nitrate of the positive electrode material within the above range, which is beneficial for the positive electrode material to have both high voltage resistance and excellent cycle stability and high capacity. Further, the content of free nitrate ions in the positive electrode material is 30ppm≤N1≤80ppm. Within this range, the formed CEI film can be further optimized, the occurrence of interfacial side reactions can be further reduced, and the impact on the capacity and electrical properties of the battery and the internal resistance of the battery can be further reduced. Illustratively, the content of free nitrate ions can be 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 70 ppm, 80 ppm, 90 ppm, 100 ppm, or any value within the range formed by any two of the above values.
[0036] In some embodiments, based on the mass of the positive electrode material, the mass proportion of the M element can be 10ppm~400ppm. The concentration of the M element in the particles is within the above range, and the concentration of the M element is moderate, which can produce effective compressive stress on the unit cell, so as to well inhibit the generation and growth of microcracks, and will not occupy the lithium position, which is conducive to further improving the capacity of the prepared battery, and further improving the structural stability of the positive electrode material, improving the cycle stability of the battery, and ensuring that the electron transfer is not blocked to improve the conductivity. Exemplarily, based on the mass of the positive electrode material, the concentration of the M element can be 10ppm, 30ppm, 50ppm, 80ppm, 100ppm, 120ppm, 150ppm, 180ppm, 200ppm, 220ppm, 250ppm, 280ppm, 300ppm, 320ppm, 350ppm, 380ppm, 400ppm or any value within the range composed of any two of the above values.
[0037] Based on the mass of the positive electrode material, the concentration X1 of the M element in the central region of the particle can be 10ppm~400ppm. Exemplarily, the concentration X1 of the M element in the central region of the particle can be 10ppm, 30ppm, 50ppm, 80ppm, 100ppm, 120ppm, 150ppm, 180ppm, 200ppm, 220ppm, 250ppm, 280ppm, 300ppm, 320ppm, 350ppm, 380ppm, 400ppm or any value within the range formed by any two of the above values.
[0038] Based on the mass of the positive electrode material, the concentration X2 of the M element in the surface area of the particle can be 10ppm~400ppm. Exemplarily, the concentration X2 of the M element in the surface area of the particle can be 10ppm, 30ppm, 50ppm, 80ppm, 100ppm, 120ppm, 150ppm, 180ppm, 200ppm, 220ppm, 250ppm, 280ppm, 300ppm, 320ppm, 350ppm, 380ppm, 400ppm or any value within the range formed by any two of the above values.
[0039] Further, based on the mass of the positive electrode material, the concentration X1 of the M element in the central region of the particle is 10ppm~50ppm, and the concentration X2 of the M element in the surface region of the particle is 300ppm~400ppm. The concentration of the M element in the central region and the surface region of the particle is within the above range, which can further reduce the unit cell volume, expand the difference between the internal and external unit cell volumes, and the contraction state of the unit cell volume of the particle is more obvious, which can further increase the compressive stress of the lattice, thereby making the structural stability of the positive electrode material stronger, reducing the cracks generated in the positive electrode material during long-term cycling, so as to achieve further optimization and improvement of the capacity, rate performance and cycle performance of the battery. Exemplarily, the concentration X1 of the M element in the central region of the particle can be 10ppm, 15ppm, 20ppm, 25ppm, 30ppm, 35ppm, 40ppm, 45ppm, 50ppm or any value within the range composed of any two of the above values. Exemplarily, the concentration X2 of the M element in the surface area of the particle can be 300ppm, 310ppm, 320ppm, 330ppm, 340ppm, 350ppm, 360ppm, 370ppm, 380ppm, 390ppm, 400ppm or any value within the range formed by any two of the above values.
[0040] In some embodiments, based on the mass of the positive electrode material, the content of free lithium ions in the positive electrode material is 400ppm~600ppm. By controlling the concentration of the free lithium ions in the positive electrode material, during the charge and discharge process, it is beneficial for the free nitrate to react with the free lithium ions on the surface of the positive electrode material to form an effective CEI film. Exemplarily, the concentration of free lithium ions in the positive electrode material can be 400ppm, 410ppm, 420ppm, 430ppm, 440ppm, 450ppm, 460ppm, 470ppm, 480ppm, 490ppm, 500ppm, 510ppm, 520ppm, 530ppm, 540ppm, 550ppm, 560ppm, 570ppm, 580ppm, 590ppm, 600ppm or any value within the range of any two of the above values.
[0041] In some embodiments, the M element includes at least one of Na, K, Rb, Cs, Be, Mg, Ca, Sr, and Ba. The metal elements in the above Group IA and Group IIA can better achieve the aforementioned technical effects.
[0042] In some embodiments, the positive electrode material further contains N element, and the N element is selected from at least one element of Zr, Ti, Al, Co, Mg, W, Ce, Y, La, Nb and Mo. By doping the positive electrode material with elements, the crystal structure of the positive electrode material can be optimized, the stability of the crystal structure can be further improved, and the electrochemical performance of the positive electrode material can be further improved. Specifically, the general formula of the positive electrode material in this application is as follows: Li a Ni b Co c Q d M (1-b-c-d-e) N e O2, where 0.95≤a≤1.2, 0.5<b≤1, 0≤c≤0.25, 0<d≤0.45, b+c+d<1, 0<e<0.1, where Q includes at least one of Mn and Al, and the types of M and N are as described above. After the M element enters the transition metal layer of the positive electrode material and occupies the site of the main element, the M element will expand the transition metal layer spacing and thus increase the unit cell volume; when the M element is enriched close to the grain surface, the unit cell volume of the surface region of the grain will be larger than that of the center region of the grain, and the stress in the surface region of the grain is larger, thereby generating compressive stress toward the center of the grain, thereby causing the grain to shrink from the surface to the center of the grain. For example, if the M element is Mg, due to Mg 2+ The ionic radius of Ni is 65 pm, while 2+ The ionic radius of Co is 72 pm. 2+ The ionic radius of Mn is 74 pm. 2+The ionic radius of Mg is 80 pm. When Mg enters the transition metal layer of the positive electrode material to replace Ni / Co / Mn elements, the Mg with a small ionic radius 2+ It will reduce the distance between transition metal layers and thus reduce the unit cell volume. When the concentration of Mg element in the central area of the particle is lower than that in the surface area, it shows a surface enrichment state. The degree of reduction in the unit cell volume in the surface area of the particle is smaller than that in the central area. As a result, the unit cell volume of the particle decreases from the surface to the center, and compressive stress is generated in the particle. This compressive stress can inhibit the volume expansion of the central area of the particle and improve the structural stability of the particle.
[0043] In some embodiments, based on the mass of the positive electrode material, the concentration X3 of the N element satisfies: 0<X3≤5000ppm. In the above positive electrode material, an appropriate amount of doping with the N element can further improve the specific capacity and cycle stability of the positive electrode material. The content of the doped N element is within the above appropriate range, which is conducive to the growth of the unit cell volume of the particles to an appropriate range, so as to further improve the specific capacity and cycle stability of the positive electrode material. If the concentration of the N element is too large, such as exceeding 5000ppm, too much N element will be enriched in the surface layer of the particles, affecting the growth of the particles, making the unit cell volume of the particles smaller, and easily causing the particles to agglomerate and adhere. In the compaction process of preparing the positive electrode sheet using the positive electrode material, it is easy to cause the cracking of the agglomerated particles, which will increase the side reaction of the electrolyte and the positive electrode material in the battery, and affect the long-term electrochemical performance of the battery; in addition, when the concentration of the N element is too high, the internal resistance of the prepared battery will increase, affecting the diffusion efficiency of lithium ions and causing the battery's charge and discharge efficiency to decrease. Exemplarily, the concentration of the N element may be 0.1ppm, 10ppm, 100ppm, 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm or any value within the range of any two of the above values. Further, the concentration of the N element may be 500ppm to 3000ppm. It is understandable that the positive electrode material may not be doped with the N element, that is, the content of the N element is 0.
[0044] In some embodiments, the particle size distribution of the positive electrode material satisfies: 1.0≤(D90-D10) / D50≤1.5, L=(D90-D10) / D50 represents the width of the particle size distribution in the positive electrode material, and by controlling 1.0≤(D90-D10) / D50≤1.5, the particle size distribution of the positive electrode material is wider, which can improve the compaction density and material activity of the material, and can improve the energy density of the material. Exemplarily, (D90-D10) / D50 can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 or any value within the range of any two of the above values.
[0045] In some embodiments, the lattice strain ε of the positive electrode material is less than 0.1%. Specifically, the lattice strain ε of the positive electrode material can be 0.095%, 0.09%, 0.05%, 0.01%, 0.005%, 0%, -0.01%, -0.05%, -0.08%, -0.10% or -0.15%, etc., and of course it can also be other values within the above range, which are not limited here. By controlling the lattice strain ε to less than 0.1%, the microcracks inside the particles can be reduced, so that the particles of the positive electrode material are not easy to crack and fail during the cycle, thereby improving the long-term cycle retention rate of the positive electrode material; it should be noted that when measuring the lattice strain of the positive electrode material, the lattice strain generated by the compressive stress caused by the lattice contraction is a negative number, and the lattice strain generated by the tensile stress caused by the lattice stretching is a positive number.
[0046] In some embodiments, the specific surface area of the positive electrode material is 0.4 m 2 / g ~0.9 m 2 / g, the specific surface area of the positive electrode material is appropriate, and the surface coating is uniform, which is conducive to reducing the direct contact between the positive electrode material and the electrolyte, thereby reducing the generation of side reactions, and is conducive to improving the cycle performance of the battery prepared with the positive electrode material, while also ensuring that the battery prepared with the positive electrode material has good discharge capacity and rate performance. Exemplarily, the specific surface area of the positive electrode material can be 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g or any value within the range formed by any two of the above values.
[0047] In some embodiments, the tap density ρ1 of the positive electrode material is 2.0 g / cm 3 ~3.0g / cm 3 The tap density of the positive electrode material is within a suitable range, which is conducive to improving the compaction of the electrode sheet containing the positive electrode material and improving the energy density of the battery. For example, the tap density of the positive electrode material can be 2.1 g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 、3.0g / cm 3Or any value within the range formed by any two of the above values.
[0048] In some embodiments, the powder compaction density ρ2 of the positive electrode material is 2.8 g / cm 3 ~4.0g / cm 3 The compaction density of the positive electrode material powder is within a suitable range, which is conducive to further improving the compaction of the electrode sheet containing the positive electrode material and improving the energy density of the battery. For example, the compaction density of the positive electrode material powder can be 2.8 g / cm 3 , 2.9g / cm 3 、3.0g / cm 3 , 3.3g / cm 3 , 3.5g / cm 3 、3.8g / cm 3 , 4.0g / cm 3 Or any value within the range formed by any two of the above values.
[0049] In some embodiments, the button cell prepared using the aforementioned positive electrode material has a structural recovery degree δ during the first week of charge and discharge: 100.00% ≥ δ ≥ 99.70%; wherein δ = θ1 / θ2*100%, θ1 is the diffraction characteristic peak position of the (003) peak at the beginning of the first week of charge, and θ2 is the diffraction characteristic peak position of the (003) peak at the end of the first week of discharge. Since the unit cell volume is in a contracted state, the stress caused by the lithium ion deintercalation during the charge and discharge process can be balanced, making the material structure more stable, which enables the positive electrode material to have a higher structural recovery ability during the charge and discharge process, so that the material can exert a higher capacity during the charge and discharge process.
[0050] In some embodiments, a secondary battery prepared using the aforementioned positive electrode material has a volume change rate of ≤6.0% after being charged to 50 SOC% and stored in a 60°C oven for 21 days, and further is 4.0%~6.0%. Exemplarily, the volume change rate of the battery can be 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.0%, or any value within the range formed by any two of the above values.
[0051] In some embodiments, the positive electrode material is a single crystal or quasi-single crystal material, that is, the smallest particle of the positive electrode material is a primary particle or a secondary particle formed by no more than five primary particles, wherein the average particle size of the primary particles is 1µm~5µm. By controlling the primary particle size of the positive electrode material within the above appropriate range, the primary particles formed are of moderate size, which is conducive to reducing the specific surface area of the particles and reducing the side reactions between the particles and the electrolyte, thereby further improving the safety and cycle life of the material; moreover, the primary particles within the above particle size range can shorten the transmission path of lithium ions, which is conducive to improving the rate performance of the battery; in addition, the primary particles of the above range size are also conducive to reducing the internal stress of the particles and reducing the risk of electrochemical polarization of lithium ions inside and outside the particles, thereby increasing the capacity of the battery prepared using the positive electrode material. Exemplarily, the average particle size of the primary particles can be 1µm, 2µm, 3µm, 4µm, 5µm, or any value within the range composed of any two of the above values.
[0052] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.
[0053] It can be understood that a single grain in the present application can be a single particle composed of a primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope, and "secondary particle" refers to a secondary structure formed by the agglomeration of multiple primary particles, showing a relatively rounded spherical morphology. "Quasi-secondary particles" refer to those formed by the adhesion of several single particles. Usually, the particle size of a single particle in the above-mentioned quasi-secondary particles is usually between 1μm and 5μm. In general, the roundness of the particles of "quasi-secondary particles" is lower than that of the above-mentioned conventional "secondary particles".
[0054] It should be further explained that the "single crystal" in the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and orientation. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more of "single crystal-like morphology" positive electrode materials, which only show a large particle size similar to a single crystal in size, which is different from a polycrystal composed of many small primary particles.
[0055] Based on the same inventive concept, the present application also provides a method for preparing the aforementioned positive electrode material, which specifically comprises the following steps: Step S1, adding a raw material containing a transition metal into nitric acid to prepare a nitrate mixed solution, and then adding a dopant solution containing an M element to the nitrate mixed solution to obtain a premixed solution, wherein the M element is selected from at least one metal element in Group IA and Group IIA of the periodic table.
[0056] Specifically, raw materials containing Ni, Co, and Mn / Al transition metals are put into nitric acid to prepare a nitrate mixed solution according to the final target molar ratio of Ni:Co:Mn / Al; then, a dopant salt solution containing the M element is added to the aforementioned nitrate mixed solution until the M element in the mixed solution reaches the expected concentration, thereby obtaining a premixed solution.
[0057] In this step, the raw material containing Ni, Co, Mn / Al can be one or more of the recovered positive electrode materials containing Ni, Co, Mn / Al, pure metals of Ni, Co, Mn / Al, hydroxides of Ni, Co, Mn / Al, and nitrates of Ni, Co, Mn / Al. Wherein, when Ni, Co, Mn / Al come from the recovered ternary positive electrode materials, specifically, the recovered ternary positive electrode materials are subjected to component detection to confirm the proportion of the main element content in the recovered material and the type and proportion of the M element present, and then the positive electrode material with the confirmed composition and the pure metal of Ni / Co / Mn / Al are prepared into a mixed salt solution according to the final target Ni:Co:Mn / Al ratio. It can be understood that in some other embodiments, the Ni, Co, Mn / Al raw materials can be commercially available metal salt solutions.
[0058] In some embodiments, the stoichiometric ratio of Ni:Co:Mn / Al in the mixed salt solution meets the range of 0.5≤Ni<1, 0<Co≤0.25, 0<Mn / Al≤0.45.
[0059] In some embodiments, the salt solution containing the M element may be at least one of phosphate, sulfate, hydrochloride, and nitrate solutions of the M element. Further, the M element may be at least one of Na, K, Rb, Cs, Be, Mg, Ca, Sr, and Ba.
[0060] Step S2, preparing the premixed solution into an oxide precursor by spray pyrolysis.
[0061] In this step, the distribution of the M element inside the precursor particles can be changed by adjusting different nozzle flow rates during the spray pyrolysis process, thereby changing the size of X2 / X1.
[0062] The specific mechanism is that in the spray pyrolysis chamber, it can be roughly divided into a first area and a second area that are interconnected. Among them, the first area is the area from the nozzle to the location of the highest temperature point, and this area is a gradually heating area. The second area is the area where the highest temperature is maintained, and this area is a constant temperature area. When the flow rate of the premixed solution flowing out of the nozzle is low, it stays in the first area for a longer time, and the droplet drying rate is slow, which is more conducive to the diffusion and uniform distribution of the M element in the droplet; when the nozzle flow rate is high, the droplet quickly passes through the heated first area to the high-temperature second area, the droplet drying rate becomes faster, and the outermost layer of water will be quickly evaporated, resulting in a gradient difference in the water concentration inside and outside. At this time, the internal water will carry the M element to the surface, thereby enriching the M element on the surface.
[0063] In this step, the temperature of the spray pyrolysis can also be controlled to control the NO 3-The mechanism is that when the spray pyrolysis temperature is high, the decomposition degree of nitrate ions is high, the residual amount of nitrate ions in the precursor will be low, and the nitrate content in the final positive electrode material will be low; on the contrary, when the spray pyrolysis temperature is low, the decomposition degree of nitrate ions is low, the residual amount of nitrate ions in the precursor will be high, and the nitrate content in the final positive electrode material will be high.
[0064] In some embodiments, the nozzle flow rate V satisfies: 300L / h<V<700L / h, the nozzle flow rate is controlled within the above range, the nozzle flow rate is suitable, and the droplets pass through the first area at a controllable rate to the second area of high temperature to achieve the control of the drying rate of the droplets, and then control the water concentration difference inside and outside the droplets within a suitable range, so that the internal water carries the M element to the surface and is enriched in the surface layer, so that the concentration difference is formed in the central area and the surface area of the precursor particles, and the distribution of the M element in the particles of the final positive electrode material satisfies: 1.2≤X2 / X1≤20. Exemplarily, the nozzle flow rate V can be 300L / h, 350L / h, 400L / h, 450L / h, 500L / h, 550L / h, 600L / h, 650L / h, 700L / h or any value within the range composed of any two of the above values. Further, the nozzle flow rate can be 350L / h~650L / h.
[0065] In some embodiments, the temperature of the spray pyrolysis is 550°C to 950°C. By controlling the temperature of the spray pyrolysis within the aforementioned range, the degree of decomposition of the nitrate ion can be controlled, and then the residual amount of the nitrate ion in the positive electrode material can be controlled, so that the content of free nitrate ions in the positive electrode material prepared using the precursor can be ensured to be 10ppm to 100ppm, so as to meet the requirements of the aforementioned positive electrode material. Exemplarily, the nitrate content of the oxide precursor is 200ppm, 500ppm, 800ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm or any value within the range composed of any two of the above values.
[0066] In some embodiments, the temperature of the first region is 60°C to 200°C. In some embodiments, the temperature of the second region is 400°C to 800°C. The temperature of the first region plays a role in preliminary drying and removes a certain amount of moisture; the temperature of the second region is higher, and the drying rate is much faster than that of the first region. The purpose is to control the migration speed of moisture by drying temperature to achieve the purpose of moisture carrying M element migration. Exemplarily, the temperature of the first region can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C or any value within the range of any two of the above values. Exemplarily, the temperature of the second region can be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C or any value within the range of any two of the above values.
[0067] In some embodiments, the concentration of nitric acid is 1% to 3%. The through hole controls the concentration of nitric acid, which can adjust the retention amount of nitrate ions in the oxide precursor, and then adjust the content of free nitrate ions in the positive electrode material prepared by the precursor to 10ppm to 100ppm, so as to meet the requirements of the above positive electrode material. Exemplarily, the concentration of nitric acid can be 1%, 2%, 3%, or any value within the range of any two of the above values.
[0068] Step S3, mixing the oxide precursor and the lithium salt and sintering them to obtain a positive electrode material matrix.
[0069] The oxide precursor is air flow-pulverized, and the particle size D50 is 2.0 μm-4.0 μm, which is beneficial to reduce the content of fine powder in the subsequently prepared positive electrode material, and the particle surface is relatively round.
[0070] In this step, a dopant containing N element may be added to the mixture of the oxide precursor and the lithium salt and sintered together.
[0071] In some embodiments, the N element may be at least one of Zr, Ti, Al, Co, Mg, W, Ce, Y, La, Nb and Mo.
[0072] In some embodiments, the lithium salt can be at least one of lithium hydroxide, lithium carbonate, and the like.
[0073] In some embodiments, based on the mass of the positive electrode material, the amount of lithium salt added is 60wt%~120wt%. By controlling the amount of lithium salt added within the aforementioned range, the concentration of the Li element on the surface of the positive electrode material can be ensured to be 400ppm~600ppm. Thus, during the charge and discharge process, nitrate ions and lithium ions can react on the surface of the positive electrode material to form an effective CEI film. Exemplarily, the amount of lithium salt added is 60wt%, 70wt%, 80wt%, 90wt%, 100wt%, 110wt%, 120wt% or any value within the range composed of any two of the above values.
[0074] Specifically, the obtained oxide precursor is mixed in a molar ratio (n (Ni+Co+Mn) :n Li =1:1) and a lithium source. After that, the mixture is placed in an atmosphere furnace and sintered once at a corresponding temperature and oxygen atmosphere. Sintering in air or oxygen atmosphere can achieve the reaction of the material with oxygen to form a target layered compound.
[0075] Among them, the sintering temperature is 880℃~980℃, and the sintering time is 4~12h. Sintering under this condition can achieve full melting of lithium salt and auxiliary materials, and fully infiltrate into the precursor, improve the uniformity of infiltration, and at the same time, during the sintering process, the particles are formed and stabilized. Therefore, by controlling the temperature and sintering time of a single sintering, it is possible to ensure that the crystal grows fully and does not over-sinter, thereby controlling the unit cell volume size to meet the required standards, thereby improving the particle strength and structural stability. Exemplarily, the sintering temperature can be 880℃, 890℃, 900℃, 910℃, 920℃, 930℃, 940℃, 950℃, 960℃, 970℃, 980℃ or any value within the range composed of any two of the above values. Exemplarily, the sintering time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value within the range composed of any two of the above values.
[0076] Step S4, crushing and coating the positive electrode material matrix to obtain the positive electrode material.
[0077] The crushed positive electrode matrix material and the coating agent are uniformly mixed and subjected to secondary sintering. This process is to improve the electrochemical properties of the positive electrode matrix material by coating. The secondary sintered positive electrode material is then screened and demagnetized to obtain a finished positive electrode material. In some embodiments, the coating element in the coating agent can be selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, Y, K, Na, etc., wherein the coating agent can be an oxide of the coating element or a lithium ion conductor.
[0078] In some embodiments, the content of the coating element may be 200ppm to 5000ppm. For example, the content of the coating element may be 200ppm, 500ppm, 800ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm or any value within the range consisting of any two of the above values.
[0079] In some embodiments, the temperature of the secondary sintering can be 400-600°C, and the sintering time can be 6-12h. By controlling the temperature and time of the secondary sintering, the coating agent can be evenly coated on the surface of the substrate in batches, further optimizing the surface structure of the positive electrode material, so as to further improve the structural stability and conductivity of the positive electrode material. Exemplarily, the temperature of the secondary sintering can be 400°C, 500°C, 600°C or any value in the range of any two values above, and the sintering time can be 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value in the range of any two values above.
[0080] An embodiment of the present application also provides a positive electrode sheet using the aforementioned positive electrode material, comprising a positive electrode collector and a positive electrode active material layer disposed on at least one surface of the positive electrode collector, wherein the positive electrode active material layer comprises the aforementioned positive electrode material.
[0081] The positive electrode current collector may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0082] The present application also provides a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing. The electrode assembly includes a separator, a negative electrode sheet and the positive electrode sheet, and the separator is disposed between the positive electrode sheet and the negative electrode sheet.
[0083] In some embodiments, the outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery. In other embodiments, the secondary battery may also be a steel-shell battery, an aluminum-shell battery, or the like.
[0084] In some embodiments, the electrode assembly may be a laminated structure, which is formed by alternately stacking a positive electrode sheet, a separator, and a negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.
[0085] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be a composite current collector disclosed in any prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium-ion battery, a sodium-ion battery, a solid electrolyte battery, etc., without limitation herein.
[0086] like Figure 1 and Figure 2 As shown in the figure, they are schematic diagrams of lithium removal and lithium insertion during the charging and discharging process of a lithium-ion battery prepared by using the positive electrode material provided in the embodiment of the present application. Figure 1 As shown in , when a lithium-ion battery is charged, lithium ions are released from the positive electrode and embedded in the negative electrode; Figure 2 As shown, when a lithium-ion battery is discharged, lithium ions are released from the negative electrode and embedded back into the positive electrode.
[0087] The embodiment of the present application controls the distribution of the M element in the particles of the positive electrode material to satisfy: 1.2≤X2 / X1≤20, and controls the content of free nitrate ions in the positive electrode material to satisfy 10ppm≤N1≤100ppm, which can effectively improve the structural stability of the positive electrode material, reduce the generation of microcracks, and form a stable interface protection layer on the surface of the positive electrode material, reduce the side reactions between the electrolyte and the surface of the positive electrode material, thereby comprehensively improving the capacity and cycle performance of the battery prepared using the positive electrode material, and improving the gas production performance. Therefore, under high voltage, the use of the aforementioned positive electrode material can effectively improve the capacity, rate and cycle stability of the battery, and improve the gas production performance. Among them, the aforementioned positive electrode material is used in a button battery with a capacity of ≥182.6mAh / g, and the cycle performance of the battery is evaluated. At room temperature (25°C), after 50 cycles of 0.5C charge and 1C discharge, the cycle retention rate is ≥95.5%, the first efficiency is ≥87%, and the volume change rate is ≤6.0%. This shows that the use of the aforementioned positive electrode materials can effectively improve the capacity and cycle performance of the battery.
[0088] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0089] Example 1 Step S1, respectively putting Ni, Co, and Mn pure metal particles into nitric acid to form a nitrate solution, and preparing the three nitrate solutions into a mixed nitrate solution according to the molar ratio of Ni:Co:Mn=60:10:30, wherein the total concentration of Ni, Co, and Mn in the solution is 5 mol / L, and then adding Mg nitrate solution to the mixed nitrate solution until the molar ratio of Mg:Ni in the mixed solution is 1:466, to obtain a premixed solution.
[0090] Step S2, spray pyrolysis of the premixed solution, wherein the nozzle flow rate is 500 L / h, the temperature of the first zone is 150° C., and the temperature of the second zone is 700° C., to obtain an oxide precursor, and gasify the obtained oxide precursor.
[0091] Step S3, weigh 500g of the above-mentioned crushed oxide precursor, 233.4g of lithium carbonate, and 2.25g of ZrO2 and mix them evenly. Sinter at 930°C for 8h in a compressed air atmosphere, crush the sintered material to a particle size of D50=4.17μm, and obtain a positive electrode material matrix.
[0092] Step S4, preliminarily mix 400g of the positive electrode material matrix with 0.67g of TiO2, sinter at 550°C for 8h in an oxygen atmosphere, and sieve the obtained material to obtain the positive electrode material. Among them, X2 / X1 of the Mg element in the positive electrode material is 7.2, and the content of free nitrate is 68ppm.
[0093] Example 2 The difference from Example 1 is that: in step S2, the temperature of the first area is increased from 150° C. to 160° C., and the temperature of the second area is increased from 700° C. to 730° C.; In step S3, the particle size of the positive electrode material matrix is D50=4.2 μm.
[0094] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 6.9, and the content of free nitrate is 12 ppm.
[0095] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0096] Example 3 The difference from Example 1 is that: in step S2, the temperature of the first zone is reduced from 150°C to 140°C, and the spray pyrolysis temperature is reduced from 700°C to 670°C; In step S3 , the particle size of the positive electrode material matrix is D50=4.15 μm.
[0097] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 8.7, and the content of free nitrate is 97 ppm.
[0098] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0099] Example 4 The difference from Example 1 is that: in step S1, a nitrate solution of Ca is added to the mixed nitrate solution until the molar ratio of Ca:Ni in the mixed solution is 1:466; In step S3 , the particle size of the positive electrode material matrix is D50=4.16 μm.
[0100] In step S4, the Ca element X2 / X1 in the obtained positive electrode material is 12.5, and the content of free nitrate is 65 ppm.
[0101] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0102] Example 5 The difference from Example 1 is that: in step S1, K nitrate solution is added to the mixed nitrate solution until the molar ratio of K:Ni in the mixed solution is 1:466; In step S3 , the particle size of the positive electrode material matrix is D50=4.16 μm.
[0103] In step S4, X2 / X1 of the K element in the obtained positive electrode material is 5.6, and the content of free nitrate is 69 ppm.
[0104] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0105] Example 6 The difference from Example 1 is that: in step S2, the nozzle flow rate during the spray pyrolysis process is reduced from 500 L / h to 300 L / h; In step S3 , the particle size of the positive electrode material matrix is D50=4.13 μm.
[0106] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 1.2, and the content of free nitrate is 72 ppm.
[0107] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0108] Example 7 The difference from Example 1 is that: in step S2, the nozzle flow rate during the spray pyrolysis process is increased from 500 L / h to 700 L / h; In step S3 , the particle size of the positive electrode material matrix is D50=4.3 μm.
[0109] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 19.2, and the content of free nitrate is 69 ppm.
[0110] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0111] Example 8 The difference from Example 1 is that: in step S1, the recovered positive electrode material containing Ni, Co, and Mn is put into nitric acid to form a mixed solution instead of pure Ni, Co, and Mn metals, and Ni(NO3)2, Co(NO3)2, and Mn(NO3)2 are added to make the Ni:Co:Mn in the mixed solution reach the target molar ratio, and the target molar ratio of Ni:Co:Mn is controlled to be 70:10:20; In step S3, 500 g of the oxide precursor, 252.6 g of lithium hydroxide monohydrate, and 2.25 g of ZrO2 were weighed and uniformly mixed, and sintered at 915° C. for 8 h in an oxygen atmosphere. The sintered material was crushed to a particle size of D50=4.21 μm to obtain a positive electrode material matrix.
[0112] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 7.3, and the content of free nitrate is 65 ppm.
[0113] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0114] Example 9 The difference from Example 1 is that: in step S1, the target molar ratio of the nitrate mixed solution is controlled to be Ni:Co:Mn=80:10:10; In step S3, 500 g of the oxide precursor, 252.6 g of lithium hydroxide monohydrate, and 2.25 g of ZrO2 were weighed and uniformly mixed, and sintered at 900° C. for 8 h in an oxygen atmosphere. The sintered material was crushed to a particle size of D50=4.3 μm to obtain a positive electrode material matrix.
[0115] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 9.3, and the content of free nitrate is 75 ppm.
[0116] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0117] Example 10 The difference from Example 1 is that in step S3, 2.25 g of ZrO2 is replaced by 0.67 g of WO3, and the particle size of the sintered material is D50=4.02 μm.
[0118] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 10.1, and the content of free nitrate is 71 ppm.
[0119] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0120] Embodiment 11 The difference from Example 1 is that in step S3, 2.25 g of ZrO2 is replaced by 1.02 g of Y2O3, and the sintered material particle size D50=4.3 μm.
[0121] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 10.5, and the content of free nitrate is 77 ppm.
[0122] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0123] Example 12 The difference from Example 1 is that in step S3, the sintering temperature after mixing is adjusted from 930°C to 920°C.
[0124] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 6.8, and the content of free nitrate is 82 ppm.
[0125] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0126] Embodiment 13 The difference from Example 1 is that in step S3, the sintering temperature after mixing is adjusted from 930° C. to 940° C.
[0127] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 7.4, and the content of free nitrate is 53 ppm.
[0128] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0129] Embodiment 14 The difference from Example 1 is: In step S2, the temperature of the first region is increased from 150°C to 155°C, and the temperature of the second region is increased from 700°C to 720°C; In step S3, the particle size of the positive electrode material matrix is D50=4.02 μm.
[0130] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 5.8, and the content of free nitrate is 32 ppm.
[0131] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0132] Embodiment 15 In step S3, the sintering temperature after mixing is adjusted from 930°C to 915°C.
[0133] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 6.4, and the content of free nitrate is 73 ppm.
[0134] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0135] Example 16 The difference from Example 1 is: In step S1, pure metal particles of Ni, Co and Al are respectively put into nitric acid to form a nitrate solution, and the three nitrate solutions are prepared into a mixed nitrate solution according to the molar ratio of Ni:Co:Al=83:12:5, wherein the total concentration of Ni, Co and Al in the solution is 5 mol / L, and then a nitrate solution of Mg is added to the mixed nitrate solution until the molar ratio of Mg:Ni in the mixed solution is 1:466 to obtain a premixed solution; in step S3, sintering at 880°C for 8h in an oxygen atmosphere, crushing the sintered material to a particle size of D50=4.10μm, and obtaining a positive electrode material matrix.
[0136] In step S4, X2 / X1 of the Mg element in the obtained positive electrode material is 11.3, and the content of free nitrate is 80 ppm.
[0137] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0138] Comparative Example 1 Step S1, preparing a mixed hydrochloride solution of three metals, Ni, Co, and Mn, according to a molar ratio of Ni:Co:Mn=60:10:30, and then adding a hydrochloride solution of Mg to the mixed hydrochloride solution until the molar ratio of Mg:Ni in the mixed solution is 1:1300, to obtain a premixed solution.
[0139] Step S2, spray pyrolysis of the premixed solution, wherein the nozzle flow rate is 500 L / h, only one temperature zone is set, and the temperature is 700° C., to obtain an oxide precursor, and the obtained oxide precursor is gasified.
[0140] Step S3, weigh 500g of the above-mentioned crushed oxide precursor, mix it evenly with 233.4g of lithium carbonate and 2.25g of ZrO2, sinter it at 930°C for 8h in a compressed air atmosphere, crush the sintered material to a particle size of D50=4.18μm, and obtain a positive electrode material matrix.
[0141] Step S4, preliminarily mix 400g of the positive electrode material matrix with 0.67g of TiO2, sinter at 550°C for 8h in an oxygen atmosphere, and sieve the obtained material to obtain the positive electrode material. The X2 / X1 of the Mg element in the positive electrode material is 1.1, and the content of free nitrate is 0ppm.
[0142] Comparative Example 2 Step S1, pure metal particles of Ni, Co and Mn are respectively put into nitric acid to form nitrate solutions, and the three nitrate solutions are prepared into a mixed nitrate solution according to a molar ratio of Ni:Co:Mn=60:10:30.
[0143] Step S2, spray pyrolysis of the aforementioned nitrate mixed solution, wherein the nozzle flow rate is 900 L / h, only one temperature zone is set, and the temperature is 600° C., to obtain an oxide precursor, and the obtained oxide precursor is gasified.
[0144] Step S3, weigh 500g of the above-mentioned crushed oxide precursor, 233.4g of lithium carbonate, 2.25g of ZrO2 and 1.25g of MgO, mix them evenly, sinter them at 550°C for 8h in an oxygen atmosphere, and sieve the obtained materials to obtain a positive electrode material. Among them, X2 / X1 of Mg element in the positive electrode material is 57, and the content of free nitrate is 147ppm.
[0145] Comparative Example 3 Step S1, synthesizing a hydroxide precursor with a ratio of Ni:Co:Mn=60:10:30 by a coprecipitation method.
[0146] Step S2, weigh 500g of hydroxide precursor and evenly mix with 211.8g of lithium carbonate, 2.25g of ZrO2 and 1.25g of MgO, sinter at 930°C for 8h in a compressed air atmosphere, crush the sintered material to a particle size of D50=4.15μm, and obtain a positive electrode material matrix.
[0147] Step S4, preliminarily mix 400g of the positive electrode material matrix with 0.67g of TiO2, sinter at 550°C for 8h in an oxygen atmosphere, and sieve the obtained material to obtain a positive electrode material. Among them, the X2 / X172 of the Mg element in the positive electrode material and the content of free nitrate are 0ppm.
[0148] Comparative Example 4 The difference from Example 1 is that in step S2, the temperature of the second temperature zone is increased from 700°C to 800°C; in step S3, the particle size D50 of the positive electrode material matrix is 4.18 μm. In step S4, the X2 / X1 of the Mg element in the obtained positive electrode material is 5.7, and the content of free nitrate is 2 ppm.
[0149] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0150] Comparative Example 5 The difference from Example 1 is that in step S2, the nozzle flow rate during the spray pyrolysis process is reduced from 500 L / h to 200 L / h; in step S3, the particle size D50 of the cathode material matrix is 4.10 μm. The X2 / X1 of the Mg element in the obtained cathode material is 1.1, and the content of nitrate is 76 ppm.
[0151] The other steps are basically the same as those in Example 1, please refer to Example 1.
[0152] The following method was used to perform performance tests on the positive electrode materials obtained in the above Examples 1-16 and Comparative Examples 1-5.
[0153] 1. The test method for the concentration of M element in the positive electrode material is as follows: Using Agilent 5110 ICP-OES equipment, 0.3 g of sample was added with aqua regia for digestion. After cooling and constant volume, 1 mL was taken and diluted 100 times to test the mass content of the main elements Li / Ni / Co / Mn, and the mother liquor was used to test the mass content of the M element.
[0154] 2. The test method for the concentration distribution of M element in the positive electrode material is as follows: The test method for the average concentration X1 of the element M in the center area and the average concentration X2 in the surface area of the positive electrode material particles is as follows: use a Hitachi ion cutting instrument to prepare a cross-section sample, use a Hitachi S4800 scanning electron microscope to select a suitable cross-section field of view, and then use EDS to perform line scanning or point scanning on the particle cross section within the 5k field of view. For example, the point scanning method can be used to measure the content of the element M at 10 positions (generally at least 5 points) in the center area of the particle cross section, and the content of the element M is summed and averaged to obtain X1; measure the content of the element M at 10 positions in the surface area of the particle cross section, and the content of the element M is summed and averaged to obtain X2. Figure 3 As shown in the particle cross-sectional view, the radius of the particle is L, the area from the center of the particle to the distance L / 2 from the center of the particle is the central area, and the area from the position L / 2 of the particle to the surface of the particle is the surface area. When the positive electrode material contains two or more elements M, X1 and X2 of each element M are measured separately, and the X2 / X1 value of the corresponding element is calculated accordingly.
[0155] For point scanning and line scanning, combined Figure 3 The instructions are as follows: Point scanning: Select 5-10 points in the central area for EDS measurement, and take the average value after measurement to get the X1 value; select 5-10 points in the surface area for EDS measurement, and take the average value after measurement to get the X2 value.
[0156] Line scan: Randomly select at least three line positions in the center area for line scan, and take the average value after measurement to get the X1 value; randomly select at least three line positions in the surface area for line scan, and take the average value after measurement to get the X2 value. In actual testing, point scan and line scan can also be used in combination.
[0157] 3. The nitrate ion content on the surface of the positive electrode material was characterized using an ICS-6000 ion chromatograph. The test method was as follows: (1) Weigh approximately 0.7 g of sample into a 70 mL beaker, accurate to 0.0001 g.
[0158] (2) Accurately measure 50 mL of ultrapure water in a 50 mL volumetric flask. First, add a small amount of ultrapure water (about 7 mL) to the sample. Stir evenly with a glass rod and then add the remaining ultrapure water. Stir evenly and then ultrasonicate for 3 minutes. Let it stand for about 17 minutes to allow the sample to settle.
[0159] (3) Use a 1 mL sterile syringe to draw the sample supernatant, inject it into the instrument through a disposable filter head, and then test it; ion chromatograph model: Thermo Scientific Dionex ICS-6000.
[0160] (4) Chromatographic setting conditions: eluent concentration: 25 mmol / L; eluent flow rate: 0.3 mL / min; column temperature: 30 ± 1 °C; detection cell temperature: 35 ± 1 °C; suppressor current: 26 mA; chromatographic column: anion exchange column (4*250 mm, AS11-HC).
[0161] (5) Data acquisition: After the baseline is stable (the signal value change is less than 0.1 μS / 20 min), use a 1 mL syringe to draw 1 mL of anion mixed solution (supernatant), click data acquisition, and the analysis will begin.
[0162] (6) Calculation of results: The calculation formula is Xi = Ci * V / M, where Xi is the mass content of nitrate ions in the sample, in mg / kg; Ci is the concentration of nitrate ions in the sample solution, in mg / L; V is the volume of the sample solution, in mL; and M is the mass of the sample, in g.
[0163] 4. The test method for the structural recovery degree δ is as follows: Electrochemical in situ XRD was used to test the structural changes of the positive electrode material during the charge and discharge process using a Bruker D8 Advance (Cu target) and a BlueDyne (5mA, 5V) device. The charge and discharge voltage range was 2.8-4.35V. The Jade software was then used to fit the XRD spectrum to obtain the diffraction angle corresponding to the (003) peak at the beginning and end of charge and discharge.
[0164] 5. Particle size test: Malvern laser particle size tester MS 3000 was used to test the particle size of the positive electrode material.
[0165] 6. The test method for the tap density ρ1 of the positive electrode material is as follows: Dandong Better BT-303 was used to test the compacted density: vibration rate 3000 times / min, vibration time 1min, vibration amplitude 3mm±0.1mm.
[0166] 7. The test method for the compacted density ρ2 of the positive electrode material powder is as follows: Using the American Carver 4350 tester, 1g of sample was weighed and placed in a mold, pressed with a pressure of 6t for 30s. After pressing, the height was tested and the compacted density was calculated.
[0167] 8. The test method for the specific surface area S1 of the positive electrode material is as follows: the specific surface area of the material is tested using the McAb 3020 nitrogen adsorption method.
[0168] Equipment: Specific surface area and pore structure analyzer.
[0169] Method: Weigh the mass of the empty sample tube m1; take 3g of sample and add it to the sample tube through a long-necked funnel; vacuum degas at 300℃ for 1h, and weigh the mass of the sample tube m2 after cooling; the mass of the sample is m=m2-m1. The sample tube is placed in liquid nitrogen, and the nitrogen adsorption amount V of the sample is measured at a series of relative pressures P / P0 to obtain the adsorption isotherm. Among them, P / P0 is set to 0.05 / 0.1 / 0.15 / 0.20 / 0.25 / 0.30. Fit the isothermal adsorption curve, calculate the monolayer saturated adsorption amount Vm according to the slope and intercept, and then calculate the specific surface area according to Vm.
[0170] 9. The test method for the average particle size of primary particles is as follows: The SEM images of the positive electrode materials were taken using Hitachi's S4800 scanning electron microscope in areas where the particles were evenly dispersed and less agglomerated. The magnification was 3k times, and the number of primary particles in a single SEM was not less than 200. The Nano Measure software was selected to open the taken SEM image, and the 2 grids in the image ruler were measured as the measuring ruler. The size of the single crystal primary particles in the SEM image was measured using the cross-hatch method, and the number of statistics was not less than 400. The average size in the final output report was the average particle size of the primary particles.
[0171] 10. Battery production and performance testing: a. Preparation of electrochemical performance test samples: Button cell production: After the ternary cathode material is mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) at a mass ratio of 80:10:10, NMP (N-methylpyrrolidone) is added to make a uniform slurry and coated on the copper foil, dried in an oven, rolled at a pressure of 10Mpa, and cut into a circular pole piece with a diameter of 14mm; the lithium-ion battery is assembled according to the CR2025 button cell in industry, the diaphragm is Cellgard diaphragm, the electrolyte is a 1mol / L LiPF6 solution with EC / PC / DEC as solvent, and the counter electrode is a lithium sheet. The entire assembly process is assembled in a glove box filled with argon gas, and the oxygen content and moisture content in the glove box are controlled below 0.5ppm.
[0172] b. Power-off test: After standing for 12 hours, perform the battery test according to the following system: After 2 weeks of 0.1C charge and 0.1C discharge, the charge cut-off voltage was 4.45V, the discharge cut-off voltage was 2.5V, and the constant voltage cut-off current was 0.005C. The first cycle capacity, discharge specific capacity and first coulombic efficiency were measured.
[0173] High voltage cycle performance test: 0.5C charge and 1C discharge, with a charge cut-off voltage of 4.45V and a discharge cut-off voltage of 2.5V, for 50 cycles, constant voltage cut-off current of 0.05C, the ratio of the measured capacity to the first cycle capacity is the 50-cycle capacity retention rate.
[0174] 11. Gas production performance test: The storage gas production performance of the positive electrode material was evaluated by using a basic soft-pack battery. The specific method is as follows: the positive electrode material, PVDF, SP, and CNT were weighed in a mass ratio of 97.0:1.0:1.5:0.5, NMP was added according to a solid content of 50%, and a high-speed dispersant was used to adjust the viscous slurry. The slurry was evenly coated on the aluminum foil with a scraper, and then dried in an oven at 80°C, and then rolled and cut into 4cm×8cm positive electrode sheets; the graphite negative electrode, SP, CMC, and SBR were weighed in a mass ratio of 96:1.0:1.2:1.8, dispersed into slurry, coated on copper foil, and cut into 4cm×8cm negative electrode sheets. The positive and negative electrode sheets were assembled into a basic soft-pack battery, charged to 50SOC% after formation, and then stored in a 60°C oven for 21 days. The volume difference before and after storage was tested by the drainage method, and the volume change rate was calculated, which was the gas production measurement index.
[0175] The corresponding test results of the positive electrode materials of Examples 1-16 and Comparative Examples 1-5 are shown in Tables 1 and 2 below.
[0176] Table 1 Table 2 like Figure 4 and Figure 5 As shown in the figure, the distribution diagram of Mg element inside the particles in the positive electrode materials prepared in Example 1 and Comparative Example 1 respectively. Figure 4 It can be seen that in Example 1, the Mg element has a concentration difference between the central area and the surface area of the single crystal particle. Figure 5 It can be seen that in Comparative Example 1, the Mg element is evenly distributed in the central area and the surface area of the single crystal particles.
[0177] Figure 6 The XPS spectrum of the Li element on the surface of the positive electrode material in Example 1 after being loaded into the battery for one week of charge and discharge. Since the positive electrode material in Example 1 contains an appropriate amount of free nitrate ions, Figure 6 It can be seen that the surface of the positive electrode material contains more Li2O phase. Figure 7 is the XPS spectrum of the Li element on the surface of the positive electrode material after being loaded into the battery and charged and discharged for one week. The positive electrode material in Comparative Example 1 does not contain free nitrate, such as Figure 7 As shown, there is only a small amount of Li2O phase on the surface of the positive electrode material.
[0178] As can be seen from Table 1-2, in Examples 1-16, the positive electrode materials all have excellent capacity, first efficiency and high-voltage cycle retention rate, with a capacity ≥182.6 mAh / g, a first efficiency ≥87.3%, and a high-voltage cycle retention rate of ≥93% after 50 cycles of 0.5C charge and 1C discharge, and a volume change rate of ≤6%. This is mainly because, in Examples 1-16, the content of free nitrate ions in the positive electrode material is regulated to be 10ppm~100ppm, and the distribution of the M element in the positive electrode material satisfies: 1.2≤X2 / X1≤20.
[0179] Compared with Example 1, the concentration of M element in the positive electrode material prepared in Comparative Example 1 is X2 / X1<1.2, and the distribution of M element in the surface particles is relatively uniform; at the same time, the content of free nitrate in the material is too low to form an effective Li2O stable interface protection layer on the surface of the positive electrode material. Therefore, the capacity, first efficiency and cycle retention rate of the battery prepared by the positive electrode material of Comparative Example 1 are all low.
[0180] Compared with Example 1, the concentration of M element in the positive electrode material prepared in Comparative Example 2 is X2 / X1>20. Excessive M element will be enriched on the surface of the particles, similar to the conventional coating effect, and has no obvious advantage in improving the material performance. It will also occupy the lattice lithium site, affecting the transmission and diffusion of lithium ions and reducing the rate performance of the secondary battery. At the same time, the content of free nitrate in the material is too high, which easily leads to the CEI film layer on the surface of the positive electrode material being too thick, which will increase the internal resistance of the battery and deteriorate the rate performance. Therefore, the capacity, first efficiency and cycle retention rate of the battery prepared by the positive electrode material of Comparative Example 2 are all low.
[0181] Compared with Example 1, in Comparative Example 3, the hydroxide precursor is synthesized by the co-precipitation method, and the M element is not doped during the precursor preparation process. Although the M element is doped in the subsequent sintering process, it is difficult to form a concentration difference between the inner and outer layer regions of the M element. At the same time, the content of free nitrate ions in the positive electrode material is 0. Therefore, the capacity, first efficiency and cycle retention rate of the battery prepared by the positive electrode material of Comparative Example 3 are all low.
[0182] Compared with Example 1, the distribution of the M element in the positive electrode material in Comparative Example 4 satisfies 1.2≤X2 / X1≤20, but the content of free nitrate in the material is too low (only 2 ppm), and it is difficult to induce the formation of a Li2O stable interface protective layer on the surface of the material. Therefore, the capacity, first efficiency, cycle retention rate and gas production performance of the battery prepared with the positive electrode material of Comparative Example 4 are all poor.
[0183] Compared with Example 1, the distribution of M element in the positive electrode material in Comparative Example 5 is X2 / X1<1.2, the distribution of M element is relatively uniform, and does not show the characteristics of different concentration gradients in the inner and outer regions of the particles. The compressive stress on the unit cell is not obvious. Therefore, the capacity, first efficiency, cycle retention rate and gas production performance of the battery prepared with the positive electrode material of Comparative Example 5 are all poor.
[0184] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material contains an M element, and the M element is selected from at least one metal element in Group IA and Group IIA of the periodic table. The positive electrode material includes a plurality of particles, and the distribution of the M element in the particles satisfies: 1.2≤X2 / X1≤20, wherein X1 is the concentration of the M element in the central region of the particle, and X2 is the concentration of the M element in the surface region of the particle; and the positive electrode material contains free nitrate ions, and the mass content of the free nitrate ions is N1, wherein 10ppm≤N1≤100ppm.
2. The positive electrode material according to claim 1, characterized in that Based on the mass of the positive electrode material, the mass proportion of the M element is 10ppm~400ppm.
3. The positive electrode material according to claim 2, characterized in that The X1 is 10ppm~50ppm; and / or, the X2 is 300ppm~400ppm.
4. The positive electrode material according to claim 1, characterized in that The distribution of the M element in the particles satisfies: 6≤X2 / X1≤11; and / or the mass content N1 of the free nitrate ions is 30ppm~80ppm.
5. The positive electrode material according to claim 1, characterized in that During the first cycle of charge and discharge, the button cell prepared from the positive electrode material has a structural recovery degree δ that satisfies: 100.00%≥δ≥99.70%, wherein δ=θ1 / θ2×100%, θ1 is the diffraction characteristic peak position of the (003) peak at the beginning of the first cycle of charge, and θ2 is the diffraction characteristic peak position of the (003) peak at the end of the first cycle of discharge.
6. The positive electrode material according to claim 1, characterized in that The general formula of the positive electrode material is as follows: Li a Ni b Co c Q d M (1-b-c-d-e) N e O2, wherein 0.95≤a≤1.2, 0.5<b≤1, 0≤c≤0.25, 0<d≤0.45, b+c+d<1, 0<e<0.1, Q includes at least one of Mn and Al, and the N element is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, Y, La, Nb and Mo.
7. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The particle size distribution width of the positive electrode material satisfies: 1.0≤(D90-D10) / D50≤1.5; (2) The lattice strain ε of the positive electrode material is less than 0.1%; (3) The specific surface area of the positive electrode material is 0.4 m 2 / g~0.9m 2 / g; (4) The tap density ρ1 of the positive electrode material is 2.0 g / cm 3 ~3.0g / cm 3 ; (5) The powder compaction density ρ2 of the positive electrode material is 2.8 g / cm 3 ~4.0g / cm 3 ; (6) The free lithium content of the positive electrode material is 400ppm~600ppm.
8. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal material, and the positive electrode material includes primary particles, and the average particle size of the primary particles is 1 μm to 5 μm.
9. A positive electrode sheet, characterized in that: The method comprises the positive electrode material as claimed in any one of claims 1 to 7.
10. A secondary battery, characterized in that: It comprises an electrode assembly, wherein the electrode assembly comprises a positive electrode sheet, a separator and a negative electrode sheet, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet comprises the positive electrode material as described in any one of claims 1 to 7.
Citation Information
Cited By
Positive electrode material, positive electrode sheet, and secondary battery
WO2026052148A1
Positive electrode material, positive electrode sheet and lithium-ion battery
WO2026138719A1